2019
DOI: 10.1177/1941738119875978
|View full text |Cite
|
Sign up to set email alerts
|

Sports-Related Concussion in Adolescent Gaelic Games Players

Abstract: Background: Gaelic games are some of the most popular sports played by Irish adolescents, and the Gaelic Athletic Association has undertaken educational initiatives to improve awareness of a sports-related concussion (SRC). However, SRC underreporting is common among adolescent athletes internationally, potentially due to poor knowledge or attitudes toward SRC. This study aimed to examine previous experiences with, knowledge of, and attitudes toward reporting SRCs, as well as views on future education in adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Sport and recreational activities are a major cause of concussions and present a serious public health concern worldwide [2,5,6]. In New Zealand, 16,994 sportsrelated concussions (SRCs) were reported in 2018-2019, comprising~48% of all reported concussions and traumatic brain injuries during that period [7]. In the USA, it has been estimated that approximately 1.6-3.8 million SRCs occur annually [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sport and recreational activities are a major cause of concussions and present a serious public health concern worldwide [2,5,6]. In New Zealand, 16,994 sportsrelated concussions (SRCs) were reported in 2018-2019, comprising~48% of all reported concussions and traumatic brain injuries during that period [7]. In the USA, it has been estimated that approximately 1.6-3.8 million SRCs occur annually [8].…”
Section: Introductionmentioning
confidence: 99%
“…Rugby union and rugby league also have high concussion rates internationally among youth athletes, with reported concussion rates ranging between 0.2 and 14.7 concussions per 1000 player-hours [ 12 ]. Of the participants surveyed in the respective studies, 48–62% of adolescent or under 20 rugby union players [ 13 , 14 ], 45% of elite rugby union players [ 15 ] and 57% of adolescents involved in the Gaelic Games [ 16 ] reported having sustained at least one SRC. Meanwhile, approximately one in five American adolescents involved in various competitive sports has reported sustaining at least one diagnosed concussion during their lifetime [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although resources and manpower may be understandably limited across different levels of play, perhaps there is a practical way to overcome this challenge. A recent survey found that over 90% of adolescent GAA players and parents would value further education on sport-related concussion [ 7 ]. We recommend that educational training programs for players, coaches, volunteers, and parents are promoted and made available at all levels of play.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a survey of 80 GAA athletes revealed that 54% reported a personal history of concussion, with 44% reporting more than one incidence [ 6 ]. Confirming this, a 2019 survey suggested that while 57.5% of GAA athletes suspected they had suffered a concussion in the past, many were undiagnosed [ 7 ]. Our recent research in Gaelic Football, another national sport in Ireland that is also governed by the GAA, reported 2.2 potential concussive events (PCEs) per match at the elite inter-county level [ 8 ].…”
Section: Introductionmentioning
confidence: 98%
“…While the helmeted sports usually draw more attention to concussion, those caring for female athletes in these sports must keep a watchful eye for hazardous activity. The research by O’Connor et al 7 demonstrates the high frequency of concussion in adolescent contact sports, recognizing that underreporting likely occurs.…”
mentioning
confidence: 99%